Scott and Bailey. Season three [videorecording (DVD)] - Jones, Suranne, 1978-; Sharp, Lesley, 1964-; Bullmore, Amelia, 1964- (BBC Worldwide, 2015)
All eight episodes from the second series of the ITV detective drama. Suranne Jones and Lesley Sharp star as two homicide detectives working for the Greater Manchester Major Incident Team. As Janet Scott (Sharp) and Rachel Bailey (Jones) investigate a string of macabre crimes across the city, they must also face up to some harsh truths in their own personal lives.